The TADISI KIRAB DUSUN MASYARAKAT DUSUN SUKOHARJO DALAM MEBANGUN KERUKUNAN ANTAR UMAT BERAGAMA - Karunia, Nanda Citra; Mustika Kartika Sari, Maya (Universitas Negeri Surabaya (Unesa), 2025)
At this time, frictions that occur between religious communities are often encountered. Therefore, it is important for the Indonesian people to participate in maintaining harmony by taking preventive measures so that various conflicts involving religion do not occur. One form of preventive action is local wisdom in the form of traditions such as the Kirab Dusun Mbah Nolo Tradition which can be found in Sukoharjo Hamlet, Penggaron Village, Mojowarno District, Jombang Regency. The purpose of this study is to describe the tradition of Kirab Dusun Mbah Nolo of the Sukoharjo Hamlet community can build inter-religious harmony. This research uses qualitative research methods with a case study design. This research data collection technique uses interviews, observation and documentation. Data analysis techniques through data collection, data reduction, data presentation and conclusion drawing. The theoretical foundation in this research is Horace Kallen's Salad Bowl theory. The result of this study is that the organization of the hamlet kirab tradition creates cooperation between religious communities. This is reflected in the process of a series of events of the kirab dusun tradition in Sukoharjo Hamlet such as deliberations on the selection of the committee and its duties and determining the time of tradition implementation. Also, various activities are carried out by cleaning the grave together, preparing a prayer place at the punden, preparing offerings, then praying together with Christian and then Islamic prayers at the grave of Mbah Nolo. This is followed by a speech and a meal together and ends with a cultural parade. The kirab tradition brings together a large kinship from the descendants of Mbah Nolo.